Animal Models for Functional Gastrointestinal Disorders - Accarie, Alison; Vanuytsel, Tim (Frontiers in Psychiatry, 2020)
Functional gastrointestinal disorders (FGID), such as functional dyspepsia (FD) and irritable bowel syndrome (IBS) are characterized by chronic abdominal symptoms in the absence of an organic, metabolic or systemic cause that readily explains these complaints. Their pathophysiology is still not fully elucidated and animal models have been of great value to improve the understanding of the complex biological mechanisms. Over the last decades many animal models have been developed to further unravel FGID pathophysiology and test drug efficacy. In the first part of this review we focus on stress-related models, starting with the different perinatal stress models, including stress of the dam, followed by a discussion on neonatal stress such as the maternal separation model. We also describe the most commonly used stress models in adult animals which brought valuable insights on the brain-gut axis in stress related disorders. In the second part, we focus on models studying peripheral, i.e. gastrointestinal, mechanisms, either induced by infection or another inflammatory trigger. In this section, we also introduce more recent models developed around food-related metabolic disorders or food hypersensitivity and allergy. Finally, we introduce models mimicking FGID resulting from surgical interventions and spontaneous models sharing characteristics of GI and anxiety-related disorders. The latter are powerful models for brain-gut axis disfunction and bring new insights about FGID and their comorbidities such as anxiety and depression.